Agriculture production, pollution emissions and economic growth from Southeast Asian perspective - Daud, Adrian; Rosli, Anita; Taasim, Shairil Izwan (Human Resource Management Academic Research Society, 2021)
The rapid increase in population worldwide is causing large scale of production of agricultural products and increased preparation of plants, livestock, vegetables and much more agricultural items for people’s use and food security. The implications from this is that, South East Asian, especially, invests in technology for large scale production for a sustainable environment. By applying the panel data analysis technique Fully Modified OLS and Dynamic OLS, this paper investigates the causal relationship between agricultural production, pollution emissions and Gross Domestic Product (GDP) among, South East Asian countries. The paper results show the variable has a long-run and short-run relationship with a positive value. While in a developing country, investment in an agricultural product based on sustainable agriculture that meets present food requirements without affecting the environment should be considered as an alternative for the benefit of future generations.